Impact of the NO Anneal on the Microscopic Structure and Chemical Composition of the Si‐Face 4H‐SiC/SiO2 Interface. Issue 12 (3rd April 2018) - Gruber, Gernot; Gspan, Christian; Fisslthaler, Evelin; Dienstleder, Martina; Pobegen, Gregor; Aichinger, Thomas; Meszaros, Robert; Grogger, Werner; Hadley, Peter
Abstract: Understanding the microscopic structure of the SiC/SiO2 interface is crucial for the improvement of SiC based metal‐oxide‐semiconductor field‐effect transistors (MOSFETs). It is well established that interface states degrade the performance and reliability of SiC MOSFETs and that passivation can be achieved by anneals in NO‐containing atmospheres. However, the structural changes associated with the NO anneal and the improvement of the channel electron mobility are still not fully understood. In this study, the SiC/SiO2 interface of the state‐of‐the art 4H‐SiC n ‐channel MOSFETs with a deposited oxide is extensively investigated with advanced scanning transmission electron microscopy (STEM) and spatially resolved electron energy‐loss spectroscopy (EELS) methods. The samples are treated with different postoxidation anneals (NO vs O2 ), resulting in strongly differing mobility and point defect density. The most notable structural difference between the samples is an increased N concentration located in the transition region between the SiC and the SiO2 of the NO‐annealed sample. The N signal is evenly distributed along the whole faceted interface and has a half‐width of w N = (1.8 ± 0.7) nm and an estimated areal density of c N = (4 ± 1) × 10 14  cm −2 . The observations support the idea that the N incorporation happens predominantly directly at the SiC/SiO2 interface where defect states are passivated. Abstract : The SiC/SiO2 interface in 4H‐SiC metal‐oxide‐semiconductor field‐effect transistors is systematically investigated by means of scanning transmission electron microscopy (STEM) and electron energy‐loss spectroscopy (EELS). The improvements in electron mobility achieved by NO‐anneals are studied to reveal changes in the microscopic interface structure. The N concentration at the interface is mapped and quantified by EELS.